Radiography of paintings: Limitations of transmission radiography and exploration of emission radiography using phosphor imaging plates. (January 2014) - Schalm, Olivier; Vanbiervliet, Lies; Willems, Peter; De Schepper, Peter
Abstract : Radiography in transmission mode is a well-established technique to visualize the internal structure of paintings. However, for many paintings the pictorial layer cannot be clearly visualized with conventional radiography because of interference from paint on the reverse, the material composition or the regular structure of supports or subsurface layers. Traditional lead white grounds in particular cause specific imaging problems not encountered with more modern white pigments such as zinc and titanium whites. A solution to this problem is radiography in emission mode. This study demonstrates and articulates those factors that can interfere with visualization of a painting's pictorial layer using transmission radiography as well as those that contribute to the effectiveness of emission radiography in visualizing such information. While emission radiography has been applied to the examination of paintings for over half a century, it is a cumbersome technique that is further complicated by the need to work under dim safelight illumination when X-radiographic film is used. Therefore, the use of computed radiography using storage phosphor imaging plates for emission radiography was also investigated.